A busca por contribuições e subsídios a um currículo de turismo no Brasil fundamentado nos princípios norteadores da ética - Schulze, Thiago Rodrigues (2011)
This work aims to investigate, identify and build contributions and aspects for a Brazilian s tourism curriculum, based on the guide principle of ethics. The work is developed considering the building of a concept of curriculum and identification of four elements which composes it, particularly the contextualization, the people, the processuality and the democratization. Elaborated the concept of curriculum, the research goes to investigate the elements which link the ethics to tourism activity. Five elements were identified: the hospitality, the sustainability, the social inclusion, the citizenship and the multiculturalism. For the building of the categories of analysis, we had observed how these five elements belong to contemporary panorama of the tourism, mainly in Brazil, based on the study of documents and publications about the theme, as well as a six months professional experience in a cruise ship. Settled the categories of analysis, we had effectuated the crossing of the four elements of curriculum and the aspects emerged from the results obtained during the study of the contemporary panorama of tourism, based on the elements of ethics in tourism. Then, the contributions and aspects for a Brazilian´s tourism curriculum, based on the guide principles of ethics, where built and identified